Scalable PBFT-like algorithm for trust management of degree/graduation certificates - ZHANG Xuewang; LEI Zhitao; LIN Jinzhao (Tongxin xuebao)
“Blockchain+education” offers a solution for trust management of degree/graduation certificates. Existing methods for managing degree/graduation certificates suffer from issues such as lacked optimization strategies for node expansion, neglect of node heterogeneity, and low through put. A scalable PBFT-like algorithm for trust management of de-gree/graduation certificates was proposed to address the above issues, called z-PBFT. The algorithm was based on a hierarchical design using regional grouping, with a model consisting of main region and sub-region node clusters. Local consensus was employed within the sub-regions. A weighted random allocation strategy based on TOPSIS modeling and entropy weighting was used to evaluate node performance and select a consensus committee node set. Analysis and simulation experiments demonstrate that the proposed algorithm ensures security while achieving higher throughput and scalability in large-scale applications of degree/graduation certificate trust management.